The Examination of mecA gene in Methicillin-Resistant Staphylococcus aureus (MRSA) and inappropriate antibiotic uses of healthcare workers and communities in Banyumas - Metta Ayu Susanti; Gembong Satria Mahardhika; Lantip Rujito; Anton Budhi Darmawan; Dwi Utami Anjarwati (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Methicillin-Resistant Staphylococcus aureus (MRSA) has become a major pathogene and its incidence continues to increase in various countries. The resistance to methicillin is caused by the mecA gene that encodes the expression of Penicillin Binding Protein 2a (PBP2a) so it has a low affinity for beta-lactam antibiotics. One of the factors that can increase the incidence of MRSA is inappropriate antibiotics use. Objective: This study is to identify presence of the mecA gene in MRSA and to compare histories of inappropriate antibiotic uses of healthcare workers and communities in Banyumas.Methods: This was a cross-sectional study conducting 120 samples from nasal swabs. Isolates of MRSA tested by bacteriological examinations and PCR of the mecA genes. Histories of antibiotic uses were assessed by using questionnaires and then analysed descriptively by using Fisher Exact test (SPPS, version 20).Result: One sample of S. aureus from the microbiology examination (0.83%) was an MRSA although there was no a mecA gene identified by using the PCR method. 66.1% of the healthcare workers and 88,3% of the communities used antibiotics inappropriately. The results showed that there was a statistically significant difference in the histories of irrational uses of antibiotics (p?0.05).Conclusion: A number of the communities who used inappropriate antibiotics was higher than the health workers. Furthermore, one MRSA strain with a negative mecA gene was found in the health worker group.